The change of content of athletic serum testosteron and cortisol in different seasons - Guo, H.; Chen, W. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
We want to observe the effect of season on athletic testosteron(T) and cortisol(C) level by testing serum contents of T and C of rowers and swimmers between June to August (A group) and December to February (B group), the purpose of this study is to give reference to sports training.